An Historical Sketch of Principal Developments in the Canon Law on Temporal Goods - Szuromi, Szabolcs Anzelm (Studia canonica, 2016)
Ecclesiastical property can be defined as those secular goods — either corporeal or non-corporeal — which belong either to the Church universal, the Apostolic See, or to other juridical person in the Church. According to St. Augustine, the Church cannot not carry out the care of numerous poor people entrusted to her or provide for their legal defense and legal service without financial support. This disciplinary tradition is the one which up to this day — with some modifications because of the changes which occurred in the Church’s social environment — determines the classification of ecclesiastical goods in the universal Church. The donations of the faithful are indispensable for divine worship, for the service of the clergy, and for the free exercise of the everyday activity and mission of the Church. Numerous normative sources from the different periods of Church history unequivocally underline that the purpose of ecclesiastical property is to secure the Church’s independent and sacred ministry for the salvation of souls.